Reindeer meat – is it always tender, tasty and healthy? - Wiklund, Eva; Malmfors, Gunnar; Finstad, Greg (Rangifer, 2007)
Meat with high pH values, so called DFD (Dark, Firm, Dry meat, is a persistent quality defect foundmin all meat species. DFD shortens shelf life, especially for vacuum-packed meat and affects meat colour, tenderness and water-holding properties. High pH values in reindeer meat have been related to pre-slaughter handling stress and poor nutritional status of the animals. There are numerous reports that variation in muscle pH and glycogen content give rise to considerable variations in meat tenderness in species such as beef and lamb. In contrast, reindeer meat has been found to be extremely tender regardless of ultimate pH. This phenomenon has been related to the speed of post mortem protein degradation and the small muscle fibre size in reindeer. Previous research has demonstrated that the fatty acid composition of meat changes in response to diets. Generally, a higher proportion of long, unsaturated fatty acids were found in meat from grazing animals compared with animals fed a grain-based diet. Reindeer meat has been found to contain moderate amounts of polyunsaturated fatty acids (PUFA), especially so-called n-3 (or omega-3) PUFAs. The PUFAs are known to be susceptible to oxidation and may therefore be easily oxidized during processing by techniques like smoking and drying. A trained sensory panel concluded that meat from reindeer fed commercial feed scored higher for liverish and sweet flavours and lower for off-flavou (i.e. ‘grass’, ‘wild’ and ‘game’) compared with meat from grazing animals. Consumer preference tests on reindeer meat showed that 50 per cent of the consumers preferred meat from grazing reindeer and 50 per cent meat from pellet-fed animals. Recent reindeer meat research has included new feed mixtures using ingredients like linseed and fishmeal. Crushed linseed in the feed gave meat with a fat composition similar to that of natural pasture, which meant more PUFA than in meat from reindeer fed the normal grain-based mixture. Fishmeal used as a protein source in reindeer feed mixtures demonstrated good feed conversion and weight gain in the animals, and sensory 72 evaluation by both a trained panel and consumers did not show any negative effects on flavour attributes of the meat. The fat composition of the meat changed just slightly when comparing fish- and soybean meal, with more PUFA in the meat from fishmeal fed animals. The control group of free-ranging reindeer had significantly highest PUFA content in the meat. Our knowledge about various factors affecting reindeer meat quality has increased significantly over the last 25 years, but there is still information missing particularly regarding the interaction between production systems, slaughter handling techniques and ultimate meat quality. Renkött - är det alltid mört, gott och nyttigt?Abstract in Swedish / Sammanfattning: Kött med höga pH-värden, DFD-kött (Dark, Firm, Dry), är ett kvalitetsproblem som kan drabba kött från alla djurslag. Detta kött har dålig hållbarhet speciellt i en vakumförpackning, men andra egenskaper som köttets färg, mörhet och vattenhållande förmåga påverkas också av DFD. Höga pH-värden i renkött har visats bero på stress i samband med slakthantering och på dålig näringsstatus hos djuren. Ett flertal undersökningar på t.ex. nöt- och lammkött har rapporterat att en variation i pH-värde och glykogeninnehåll har stor betydelse för köttets mörhet. Renkött har däremot visats vara mycket mört oberoende av pH-värde, vilket har förklarats bero på en hög aktivitet av proteinnedbrytning efter slakt men också på små muskelfibrer i renköttet. Tidigare undersökningar har demonstrerat att fettsyrasammansättningen i kött förändras beroende på vad djuren äter. Allmänt gäller att i kött från betande djur finns en högre andel fleromättade fettsyror (PUFA) jämfört med djur som utfodrats med spannmålsbaserade foder. Renkött har visats ha en relativt hög andel PUFA och särskilt de sk. omega-3 PUFA. En tränad smakpanel bedömde att kött från renar som utfodrats med kommersiellt renfoder smakade mer lever och sött och hade mindre bismaker (som t.ex. gräs, vilt och ren) jämfört med kött från naturbetande renar. I en konsumentundersökning av samma typer av renkött föredrog 50 procent av konsumenterna beteskött och 50 procent föredrog kött från utfodrade renar.Den senaste forskningen har studerat nya foderblandningar där ingredienser som linfrö och fiskmjöl har utvärderats. Linfrökaka som tillsats i renpellets gav köttet en fettsammansättning som påminde om den i kött från naturbetande renar, d.v.s. köttet innehöll mer PUFA än kött från renar som utfodrats med normala pellets. I försök där fiskmjöl har använts som proteintillskott i renfoder visades ett bra foderutnyttjande och god tillväxt hos renarna och inga negativa effekter på renköttets smak kunde påvisas varken av en tränad smakpanel eller vid en konsumentundersökning. Fettsammansättningen i köttet påverkades marginellt av tillsatsen av fiskmjöl jämfört med normalfodret baserat på sojaprotein. Kött från kontrollgruppen av naturbetande renar hade det signifikant högsta innehållet av PUFA. Kunskapen om de olika faktorer som påverkar renköttets kvalitet har ökat påtagligt under de senaste 25 åren, men fortfarande saknas en del fakta när det gäller sambanden mellan produktionssystem, slakthantering och köttkvalitet.
Keywords: reindeer meat